OVERLAND FLOW TO AND THROUGH A SEGMENT OF UNIFORM RESISTANCE - Rose C.W.; Hogarth W.L.; Ghadiri H.; Parlange J.Y.; Okom A. (My University, 2002)
Recognising the utility of grass buffer strips in sediment retention, a fundamental hydraulic interpretation of flow through such strips is sought. In order to ensure reproducibility of results, a model porous resistive element consisting of beds of nails of various densities was used to simulate the hydraulic resistance offered by grass strips. In 14 experiments, the hydraulic consequences were measured for steady flow in a flume through nail beds of various densities at various flume slopes. A newly devised staining technique was used to measure the spatial variation in water depth to and through the resistive element. Provided nail density was not too low or slope too high, the maximum depth of water occurred as flow entered the nail bed. In such cases, momentum theory was able to provide a reasonably good prediction, both of the shape of the water profile within the nail bed, and of the slope and extent of the region of hydraulic adjustment formed upslope of the resistive element.
Keywords: BUFFER STRIP; FILTER STRIP; MOMENTUM CONSERVATION; OVERLAND FLOW; HYDROLOGY